Information for the Malaysian Asphalt Industry towards better pavement interlayer bonding - Haryati Yaacob,; Mohd Rosli Hainin,; Ahmad Safuan,; Fung, Lung Chang (Universiti Kebangsaan Malaysia, 2014)
Quality of bond between layers of asphaltic concrete course is a key element to ensure the performance of a modern asphalt pavement. A proper interlayer bond ensures the structural integrity of the pavement and prevents possible distresses from occurring within the designed service life. In Malaysia, delamination is a common distress related to insufficient degree of adhesion though slippage failure can be occasionally encountered. Generally, bond development is closely related to the design factors and construction factors. This paper however focused on the construction factors only, hoping to provide some useful information which might be overlooked by the contractors during construction but is of extreme important especially in enhancing the bond development in the asphalt layers. The construction factors in particular interest discussed in this paper include curing time of asphalt emulsion, surface condition of a pavement and technology and quality of workmanship and construction. It is important to note that both design factors and construction factors are inter-related in optimizing the degree of adhesion. Thus, all factors need to be carefully identified and fulfilled in order to maximize the bond strength between pavement surfacing layers for a better quality and longer service life of pavement in Malaysia.